PENERAPAN PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS VI - Lisyalama, Amalia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to improve the quality of Indonesian language learning, especially in the material of listening, reading, and understanding the legend of the Komodo Princess. The Problem-Based Learning (PBL) model was chosen because it is considered capable of creating an innovative and interactive learning atmosphere, so that students can be more active in the learning process. The main focus of this study is how the application of PBL can facilitate the development of critical thinking skills, collaborative, and creativity of students in understanding the legend. The method used in this study is Classroom Action Research (CAR) which is carried out in several cycles until the success indicator is achieved. The study involved 9 sixth grade students of SD Negeri 002 Tanjung Perangat as research subjects. Each learning cycle applies PBL steps that are integrated with innovative and interactive elements, and are adjusted to class dynamics and student characteristics. All stages of learning are evaluated through formative and summative assessments to determine the development of students' understanding and analytical skills towards the legend of the Komodo Princess. Based on the results of the study, there was a significant increase in the category of learning outcomes and student activity from pre-cycle to cycle II, where the percentage of students in the